Carbon, Nitrogen and Phosphorus Cycling in Forest Soils - Qualls, Robert G. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The majority of carbon stored in the soils of the world is stored in forests. The refractory nature of some portions of forest soil organic matter also provides the slow, gradual release of organic nitrogen and phosphorus to sustain long term forest productivity. Contemporary and future disturbances, such as climatic warming, deforestation, short rotation sylviculture, the invasion of exotic species, and fire, all place strains on the integrity of this homeostatic system of C, N, and P cycling. On the other hand, the CO2 fertilization effect may partially offset losses of soil organic matter, but many have questioned the ability of N and P stocks to sustain the CO2 fertilization effect.